(3eNJUQ cJGH GdGYJeGO aj GdCOhjI GdeaQOIs - (3GdTfThQj , eMeO Hf YHO Gddg Hf Ydj,J (B983 (3g` s
(3ChdgG (B:s
(3cJGH GdGYJeGO eeG Cdag (B, (3GHf GdLRGQ hbO CQOJ Cf GNJUQ efg TjFkG ai HjGf HYV GdCOhjI , hHOd HYVgG , hfSCd Gddg GdEYGfI Bejf s
(3BNQgG (B:s
(3hEfeG CNJUQfG GdHYV hJQcfG GdHYV hQJHfGg Ydi MQha GdeYLe , hgh CbQH Edi GdeWGdYI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B155 - (3U(B161s
(3GdejcQhajde eabhOs
(3cJGH GdEYJeGO dCMeO Hf EHQGgje Hf CHj NGdO GHf GdLRGQ GdbjQhGfi GdeJhai (B361 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B239 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B226s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B225 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs